Internationalization of SMEs; Evidence from Mexican Leather Footwear Industry - Y. D. Cisneros-Reyes; D. C. Caldera-Gonzalez; M. G. Arredondo-Hidalgo (Technium Social Sciences Journal, 2020)
Despite Mexican leather footwear industry is traditional, it has not increased or even maintained the level of competitiveness in the global market; the export problems of SMEs (Small and Medium Enterprises) have been studied by some authors but the internationalization (beyond exports and imports and including foreign direct investment, international subcontracting and international technical cooperation) has not been deeply explored so it is not documented how the process of this economic segment is occurring and if that is evolving accordingly to the theory (E.g. Uppsala model). The objective of this study is to analyze the internationalization of SMEs of the Mexican leather footwear industry to know if accumulated knowledge and experience in foreign markets effectively leads the organization to more advanced and complex stages of international exchange. A survey composed by 47 questions was applied to a sample of 21 SMEs of the Mexican leather footwear industry, their experience was also collected by semi-structured interviews. Results show that SMEs are involved in the internationalization process strongly oriented to the development of exports and imports and only a small number of them have been able to reach the stage of foreign direct investment. These results suggest that internationalization is only conceived in terms of imports and exports and efforts are carried out only to those stages even if SMEs could obtain a great benefit from the rest of the internationalization exchange (FDI, international subcontracting and technical cooperation). This behaviour might be due to some factors as: (1) the relatively low level of competitiveness of the Mexican firms in the global industry, (2) the lack of know-how and (3) the vision of the owners and managers of the company.